Climatic reconstruction for the Younger Dryas/Early Holocene transition and the Little Ice Age based on paleo-extents of Argentière glacier (French Alps). (1st October 2019) - ,; Aumaître, Georges; Bourlès, Didier L.; Keddadouche, Karim; Protin, Marie; Schimmelpfennig, Irene; Mugnier, Jean-Louis; Ravanel, Ludovic; Le Roy, Melaine; Deline, Philip; Favier, Vincent; Buoncristiani, Jean-François
Abstract: Investigation of Holocene extents of mountain glaciers along with the related naturally-driven climate conditions helps improve our understanding of glacier sensitivity to ongoing climate change. Here, we present the first Holocene glacial chronology in the Mont-Blanc massif (Argentière glacier) in the French Alps, based on 25 in situ -produced cosmogenic 10 Be dates of moraines and glacial bedrocks. The obtained ages from mapped sequences of moraines at three locations reveal that the glacier retreated from its Lateglacial extent and oscillated several times between ∼11.7 ka and ∼10.4 ka, i.e. during the Younger Dryas/Early Holocene (YD/EH) transition, before substantially retreating at ∼10.4 ka. Climate conditions corresponding to the past extents of Argentière glacier during the YD/EH transition (∼11 ka) and the Little Ice Age (LIA) were modelled with two different approaches: by determining summer temperature differences from reconstructed ELA-rises and by using a Positive Degree Day (PDD) mass-balance model. The ELA-rise reconstructions yield a possible range of temperatures for the YD/EH transition that were lower by between 3.0 and 4.8 °C compared to the year 2008, depending on the choice of the ELA sensitivity to temperature. The results from the PDD model indicate temperatures lower by ∼3.6–5.5 °C during the YD/EH transition than during the 1979–2002 period. For the LIA, our findings highlight the role of local precipitation changes, superimposed on the dominant temperature signal, in the detailed evolution of the glacier. Overall, this study highlights the challenge that remains in accurately inferring paleoclimate conditions from past glacier extents. Highlights: Argentière glacier oscillated 5 times between 11.7 ka and 10.5 ka. Modeled Early Holocene temperature range is 3.6–5.5 °C below modern values. Local precipitation changes explain detailed Little Ice Age glacier fluctuations.